Perkembangan dan Prospek Danareksa Syariah dalam Industri Pasar Modal Syariah : Systematic Literature Review - Ricky Setiawan P; Nurul Huda (Journal of Mandalika Literature, 2025)
This study explores the growth and future prospects of Danareksa Syariah within the Islamic capital market industry in Indonesia. Danareksa Syariah, as an investment tool that complies with Syariah principles, has become increasingly popular among investors, largely due to a growing awareness of the importance of aligning investments with Islamic financial guidelines. The research employs a systematic literature review methodology based on the PRISMA 2020 framework, analyzing articles published between 2018 and 2024. The findings suggest that Danareksa Syariah has significant potential for further expansion, positioning itself as an essential component of Indonesia’s Islamic capital market. However, several challenges continue to impede its growth, including low levels of financial literacy, susceptibility to market fluctuations, and the need for more robust regulatory frameworks to ensure sustainable development. Addressing these obstacles is crucial for maximizing the potential of Danareksa Syariah, as it could play a pivotal role in supporting Indonesia's broader economic growth. Enhanced educational initiatives, improved market stability, and strengthened regulations could all contribute to further solidifying the position of Danareksa Syariah within the Islamic capital market, ensuring its ability to meet the evolving needs of investors and foster economic resilience in Indonesia.